2017
DOI: 10.15694/mep.2017.000037
|View full text |Cite
|
Sign up to set email alerts
|

The academic environment and approach to learning effects on academic performance among Sudanese medical students

Abstract: Background: Academic environment and approach to learning play a significant role in academic achievement. In this study, we aimed to assess the educational environment and approach to learning in the clinical phase medical students. Subjects and Methods: This comparative cross-sectional study conducted among 59 medical students in Omdurman Islamic University from June to August 2016. Participants signed a written informed consent then responded to a structured questionnaire to collect demographic data, the DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It has also been used to compare the curricula in transition. 4,5,11,13,[15][16][17][18][19] Very few studies have looked into the perspective of stakeholders other than the students such as the teaching faculty. In contrast to this study findings, Shahnaz and colleague reported similar perception of faculty and students on DREEM in an integrated curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used to compare the curricula in transition. 4,5,11,13,[15][16][17][18][19] Very few studies have looked into the perspective of stakeholders other than the students such as the teaching faculty. In contrast to this study findings, Shahnaz and colleague reported similar perception of faculty and students on DREEM in an integrated curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Evidence suggests that a favourable learning environment results in positive learning outcome. 4,5 Maintaining quality and validity in the educational curricula, the evaluation of the educational environment at both academic and clinical sites is important for maintaining and improving the quality of educational curriculum. 6,7 It has been advocated that a positive learning environment enhances students' motivation, promotes knowledge and skills.…”
Section: Introductionmentioning
confidence: 99%
“…The DREEM instrument is a validated Likert-type inventory tool which has the advantages of self-administration to respondents and usefulness in assessing a particular learning environment. (26,27) There are five major domains in the questionnaire with each specifically measuring an area relevant to the assessment of the learning environment. The domains are; students' perception of learning; SPL (12 items with a maximum score of 48), students' perception of course organisers; SPCO (11 items with a maximum score of 44), students' academic self-perception; SASP (8 items with a maximum score of 32), students' perceptions of atmosphere; SPA (12 items with a maximum score 48) and students' social self-perceptions; SSSP (7 items with a maximum score of 28).…”
Section: Measurement Of Students' Perception Of Learning Environment;mentioning
confidence: 99%